Differences in natural gamma radiation characteristics of Erinpura and Malani granites in NW India - Scharfenberg, Lars; Jandausch, Sebastian; Anetzberger, Lina; Regelous, Anette; Sharma, Kamal K.; de Wall, Helga (Journal of Earth System Science, 2019)
In NW India, large volumes of exposed Neoproterozoic basement rocks are formed by two magmatic suites, Erinpura granites as a late thermal event with respect to the ∼ 1 Ga Delhi Orogeny and the younger Malani igneous suite (770–750 Ma). Average uranium and thorium equivalent concentrations (in ppm) inferred from spectroscopic gamma radiation survey are higher in Malani rocks (Th 47.33 ppm and U 6.95 ppm) as compared to the Erinpura granites (Th 33.55 ppm and U 4.77 ppm). These values are considerably above the granite world average (Th 14.8 ± 13.2 ppm; U 3.93 ± 3.27 ppm). High U (up to 19 ppm) and Th (up to 88 ppm) in some Malani granites and a constant Th–U ratio of 7 points to a high degree of fractionation of the felsic magma. Higher radioelement concentration in the east (Mirpur granite) as compared to the west (Jaswantpura granite) is substantiated by geochemical data. Areas to the west and east of the Sirohi frontal thrust show differences, most likely a consequence of anatexis in the eastern sector. A high linear correlation between inductively coupled plasma mass spectrometry and gamma-ray data underlines the suitability of in-situ measurements for the determination of U and Th concentrations during a field survey providing basic information for future petrogenetic and risk-hazard studies in this granitic terrain.
CRIS-Team Scopus Importer:2019-05-28
Keywords: granitoids; Natural gamma radiation; NW India; thorium; uranium